Understanding Blended Learning Strategy in Increasing Students Motivation After Reopening Schools - Nuah Perdamenta Tarigan; Budi Sulistiyo Nugroho; Lela Susanty; Khasanah Khasanah; Fety Surfaifel (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2021)
This exploration is expected to search many insightful articles on mixed helping blended learning strategies to upgrade understudy learning results in complex and routine circumstances. To all the more likely comprehend and scholarly involvement in mixed learning, we accumulated information and data by doing a virtual information search on some notable distributions on educational issues and utilizing innovation to improve learning results. We utilized the expressions